Species‐Specific Quantitative Proteomics Profiles of Sarcoma Patient‐Derived Models Closely Reflect Their Primary Tumors. Issue 6 (4th September 2019) - Shiozawa, Kumiko; Oyama, Rieko; Takahashi, Mami; Kito, Fusako; Hattori, Emi; Yoshida, Akihiko; Kawai, Akira; Ono, Masaya; Kondo, Tadashi
Abstract : Purpose: The purpose is to examine whether patient‐derived sarcoma models recapitulate the spectrum of sarcoma heterogeneity seen in patients. Experimental design: To characterize patient‐derived models for functional studies, proteomic comparisons with originating sarcomas representative of three intrinsic subtypes by MS are performed. Results: Human protein profiling is found to be retained with high fidelity in patient‐derived models. The protein profiles of patient sarcoma tumors and mouse stroma are characterized by species‐specific quantitative proteomics. Protein‐expression levels in mouse stroma are affected by the primary human tumor. The levels of stromal proteins derived from tumors are lower in PDXs and cell lines, and some human stromal proteins are replaced by the corresponding mouse proteins in PDXs. Conclusions and clinical relevance: These findings suggest that the effects of the microenvironment on drug responses may not reflect those in the primary tumor. This cross‐species proteomic analysis in PDXs can potentially improve preclinical evaluation of treatment modalities and enhance the ability to predict clinical trial responses.